Peran Lulusan Prodi PGMI IAIN Curup dalam Tracer Study Untuk Meningkatkan Perkembangan Madrasah Ibtidaiyah di Wilayah Kabupaten Rejang Lebong - Ratnawati Ratnawati; Baryanto Baryanto (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to determine: Role, Steps and Inhibiting and Supporting Factors of PGMI graduates in improving the development of Madrasah Ibtidaiyah (MI) based on Tracer Study in Rejang Lebong Regency.This research method is descriptive qualitative. Data collection was carried out using questionnaires.. The results showed that: 1) graduates of MI of State Islamic Institute Curup have made improvements to the development of MI, 2) The steps of PGMI graduates in improving the development of Madrasah Ibtidaiyah (MI) based on Tracer Study in Rejang Lebong Regency are by providing services immediately, accurate and satisfying, always improves the quality of work, increases both intra-curricular and extra-curricular activities, self-development, improve the quality of education and management of Madrasah Ibtidaiyah. 3) The supporting factors for PGMI graduates in improving the development of MI in Rejang Lebong are; a. ; The quality of education at the Madrasah Ibtidaiyah level, there has been a BOS (School Operational Assistance) fund program, teachers of MI are on average S1 qualified, b. Obstacle factors ; Limited facilities, Some rooms are fragile and not suitable, Some of the equipments are not in accordance with the needs and characteristics of the madrasah.